Optimization and Characterization of Wood Vinegar Produced by Shorea laevis Ridl Wood Pyrolysis - Hasan Ashari Oramahi; Tsuyoshi Yoshimura; Elvi Rusmiyanto; Kustiati Kustiati (Universitas Gadjah Mada, 2020)
In this study, the Box-Behnken Design (BBD) was employed to investigate the effects of wood particle size, pyrolysis temperature, and pyrolysis time on the production of wood vinegar from Indonesia “bengkirai” wood (Shorea laevis Ridl). Characterization of wood vinegar was conducted by gas chromatography-mass spectrometry (GC-MS). Three variable designs consisting of wood particle size (2.00, 2.38, and 3.36 mm), pyrolysis temperature (350, 400, and 450 °C), and pyrolysis time (105, 120, and 135 min) were employed in a BBD response surface methodology (RSM-BBD). RSM-BBD results suggested that maximum wood vinegar yield would be obtained with a wood particle size of 3.85 mm, pyrolysis temperature of 400 °C, and pyrolysis time of 93 min. In addition, the mathematical model indicated the maximum wood vinegar yield would be 30.31%. The main compounds in wood vinegar were acetic acid, 1-hydroxy-2-propanone, furfural, 2,3-pentanedione, phenol, 2-methoxy phenol, 2-methoxy-4-methyl phenol, 2,6-dimethoxy phenol, and 1,2,4-trimethoxybenzene.